Chapter Il peso delle emozioni nell'argomentazione sui social media - Tuccini, Gianmarco (Communication and Philosophical Cultures. Researches and Instruments, 2021)
Social media are nowadays fertile ground for debates that are often rich in arguments of persuasive value. In the present writing, we hypothesize that emotions play a significant role in determining the success of arguments on social media. In order to validate the hypothesis, we analyzed Change My View, an Internet forum on Reddit where the persuasiveness of the discussions among participants is explicit and regulated by specific norms. Our analysis revealed that arguments enjoying a higher degree of success were characterized by two particular emotions: anticipation and joy, which we interpret as belonging to engagement, a more general emotional dimension that includes them both. Such characteristics of successful arguments lead us to consider the persuasive experience on social media as analogous to a playful experience. Like in a game, in order to successfully take part in such a persuasive experience, certain requirements are needed: commitment and respect for the rules as well as joyful participation.